Case Report: Adjuvant image-guided radiation therapy reduces surgical invasiveness in malignant peripheral nerve sheath tumors - Harikar, Mandara M.; Ferini, Gianluca; Palmisciano, Paolo; Shakir, Muhammad; Amico, Paolo; Ferraresi, Stefano; Umana, Giuseppe E. (Frontiers in Oncology, 2023)
Introduction Malignant peripheral nerve sheet tumors (MPNSTs) are a group of aggressive soft tissue sarcomas (STS) of mesenchymal origin. These tumors generally require extensive local excision owing to their aggressive potential. Though the role of radiotherapy is controversial, in this report, we present the case of an MPNST of the forearm that was treated with microsurgery followed by image-guided radiation therapy to achieve complete tumor disappearance at the 1.5-year follow-up. Case Report A 69-year-old woman with underlying schizoid personality disorder was referred to our department with pain, severe swelling, and ecchymosis of her right forearm. Physical examination showed hypoesthesia in the segments innervated by the median nerve and reduced motor strength of her right hand. A gadolinium-enhanced MRI showed a large malignant peripheral nerve sheath tumor (13 x 8 x 7 cm) of the median nerve in the forearm. She underwent microsurgical en-bloc tumor resection with the median nerve being spared. Thirty-five days postoperatively, she underwent image-guided radiotherapy (IGRT) using volumetric modulated arc therapy (VMAT). Serial MRI scans of the forearm with Gadolinium and whole-body CT scan with contrast enhancement at 30 days, 6 months, 1 year, and 1.5 years postoperatively documented no tumor recurrence, remnants, or metastases. Conclusions In this report, we demonstrate the successful use of advanced radiotherapy techniques such as IGRT while avoiding demolitive surgery for MPNST. Though a longer follow-up is necessary, at the 1.5-year follow-up, the patient demonstrated good outcomes of surgical resection followed by adjuvant RT for MPNST of the forearm.